2016
DOI: 10.1093/infdis/jiw461
|View full text |Cite
|
Sign up to set email alerts
|

Redeploying β-Lactam Antibiotics as a Novel Antivirulence Strategy for the Treatment of Methicillin-ResistantStaphylococcus aureusInfections

Abstract: Innovative approaches to the use of existing antibiotics is an important strategy in efforts to address the escalating antimicrobial resistance crisis. We report a new approach to the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections by demonstrating that oxacillin can be used to significantly attenuate the virulence of MRSA despite the pathogen being resistant to this drug. Using mechanistic in vitro assays and in vivo models of invasive pneumonia and sepsis, we show that oxacillin-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 32 publications
9
32
0
Order By: Relevance
“…Recovery of growth in media supplemented with oxacillin or cefoxitin alone was evident after 8 h (Fig. 3), reflecting the selection and expansion of HoR mutants as described previously [2, 18, 20]. Recovery of growth in cultures exposed to DCS alone was also evident (Fig.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Recovery of growth in media supplemented with oxacillin or cefoxitin alone was evident after 8 h (Fig. 3), reflecting the selection and expansion of HoR mutants as described previously [2, 18, 20]. Recovery of growth in cultures exposed to DCS alone was also evident (Fig.…”
Section: Resultssupporting
confidence: 74%
“…This results in significant morbidity and mortality, with up to 20% of patients with systemic methicillin resistant S. aureus (MRSA) infections dying, despite receiving treatment with anti-staphylococcal drugs [1]. As part of our efforts to identify improved therapeutic approaches for MRSA infections, we recently described the novel use of β -lactam antibiotics to attenuate the virulence of MRSA-induced invasive pneumonia and sepsis [2]. We demonstrated that oxacillin-induced repression of the Agr quorum-sensing system and altered cell wall architecture resulted in downregulated toxin production and increased MRSA killing by phagocytic cells, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed methods of synergy between β‐lactams and vancomycin are summarized elsewhere . In addition, β‐lactams synergize with innate host defense peptides against MRSA and attenuate MRSA virulence . While in vitro and in vivo support for adjuvant β‐lactam therapy for MRSA continues to grow, few studies have examined the impact of empiric adjuvant β‐lactam therapy on clinical outcomes in patients with MRSA bloodstream infection, but the results of these studies are encouraging …”
Section: Discussionmentioning
confidence: 99%
“…23,24 In addition, b-lactams synergize with innate host defense peptides against MRSA and attenuate MRSA virulence. 25,26 While in vitro and in vivo support for adjuvant b-lactam therapy for MRSA continues to grow, few studies have examined the impact of empiric adjuvant b-lactam therapy on clinical outcomes in patients with MRSA bloodstream infection, but the results of these studies are encouraging. 14,15 MRSA bloodstream infecƟon treated with vancomycin (VAN) n=201 A retrospective, single-center cohort study demonstrated that empiric, adjuvant b-lactam therapy led to an enhanced rate of microbiologic eradication compared to vancomycin alone (96% compared to 80%, respectively; p=0.021).…”
Section: Discussionmentioning
confidence: 99%